Institutional network relationships and environmental governance in the Colombian and Peruvian Amazon - Gonzalez-Rodriguez, Carlos Eduardo; Buitrago-Bermúdez, Oscar; Le Coq, Jean-Francois; Gonzalez, Carolina; Castillo-Rivera, Johana Marcela (Springer, 2025)
The Amazon—the most biodiverse biome in the world—faces huge conservation challenges. Multiple institutional and technological actors, organized in environmental networks, collaborate to support improved environmental governance. However, these efforts are understudied and underrecognized, particularly in the case of the Colombian and Peruvian Amazon. Employing a social network analysis, this study evaluates the actors, the institutional–technological relationships, and the network addressing socio-environmental challenges. We identified 392 development actors (nodes) with different levels of international, national, and regional participation. They use transnational technologies, but have limited integration of local actors where environmental challenges are most pressing. To combat the biome's rapid degradation, these countries could strengthen their environmental agendas, governance, and policy design—for greater environmental impact—by effectively integrating cooperation between international and local partners. Both countries should develop their local networks, create participatory collaborative spaces to enhance national capacities, and promote diverse and coordinated coalitions.